Expert Ignorance - Desai, Deval (Cambridge University Press, 2024)
Adopting an interdisciplinary approach, Deval Desai presents the novel concept of 'expert ignorance', a practice by which experts continually admit the limits of their knowledge. With a range of illustrative case studies, Desai demonstrates the impact of this powerful yet paradoxical form of expertise in rule of law reform and beyond.